Differentiated Approach to the Mucolytic Therapy for Respiratory Diseases in Children - Ye.I. Yulish (Zaslavsky O.Yu., 2013)
This paper presents the mechanisms of disorders of mucociliary clearance in the tracheobronchial tree in respiratory diseases in children. The authors considered differentiated approach to the prescription of mucoactive and mucolytic drugs, in particular ambroxol.